International Humanitarian Law on New Weapons - I. I. Коtlyarov (Московский журнал международного права, 2009)
The author analyses Art. 36 (New weapons) of the Additional Protocol I to the Geneva Conventions of 12 August 1949. The term “new weapons” should be considered in the context of currently existing groups of weapons, taking into consideration that the use of some weapons is limited during armed conflicts while the use of others is permitted. In the author’s opinion, the absence of the term “new weapons” definition in the art. 36 produces difficulties and hinders implementation of the article. The author introduces his definition of the term and discloses its contents. Extensive attention is paid to the need of prohibition of space weapons as a type of new weapons.